The Fusion Glycoprotein of Human Respiratory Syncytial Virus Facilitates Virus Attachment and Infectivity via an Interaction with Cellular Heparan Sulfate - Feldman, Steven A. (American Society for Microbiology, 2000)
Human respiratory syncytial virus (RSV) F glycoprotein (RSV-F) can independently interact with immobilized heparin and facilitate both attachment to and infection of cells via an interaction with cellular heparan sulfate. RSV-glycosaminoglycan (GAG) interactions were evaluated using heparin-agarose affinity chromatography. RSV-F from A2- and B1/cp-52 (cp-52)-infected cell lysates, RSV-F derived from a recombinant vaccinia virus, and affinity-purified F protein all bound to and were specifically eluted from heparin columns. In infectivity inhibition studies, soluble GAGs decreased the infectivity of RSV A2 and cp-52, with bovine lung heparin exhibiting the highest specific activity against both A2 (50% effective dose [ED(50)] = 0.28 ± 0.11 μg/ml) and cp-52 (ED(50) = 0.55 ± 0.14 μg/ml). Furthermore, enzymatic digestion of cell surface GAGs by heparin lyase I and heparin lyase III but not chondroitinase ABC resulted in a significant reduction in cp-52 infectivity. Moreover, bovine lung heparin inhibited radiolabeled A2 and cp-52 virus binding up to 90%. Taken together, these data suggest that RSV-F independently interacts with heparin/heparan sulfate and this type of interaction facilitates virus attachment and infectivity.